DOI: 10.11606/t.85.2018.tde-16022018-150129
|View full text |Cite
|
Sign up to set email alerts
|

<sup>89</sup>Zr-Imuno-PET/<sup>111</sup>In-Imuno- SPECT: desenvolvimento radiofarmacêutico de agentes de imagem molecular para receptores EGF

Abstract: BENEDETTO, Raquel. 89 Zr immuno-PET/ 111 In imuno-SPECT: Radiopharmaceutical development of molecular imaging agents for EGF receptors. 200 p. Thesis (Doutorado em Tecnologia Nuclear) Instituto de Pesquisas Energéticas e Nucleares-IPEN-CNEN/SP. São Paulo: 2017. The low selectivity of conventional methods for cancer diagnosis and therapy, as well as the fact that these methods could not achieve the desired therapeutic success, constitute difficulties for the oncological practice. In this regard, radiolabeled mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similar to in vitro results, a correlation was observed between EGFR expression and tumor uptake of 89 Zr-DFO-cetuximab by small animal PET/CT imaging as shown in Figure 5. Benedetto 59 previously performed the blocking study, and the small animal PET/CT images have revealed a reduction in uptake profile for ''blocking'' group (with an excess of unlabeling cetuximab) and an intense 89 Zr-DFO-cetuximab uptake in FCS for ''non-blocking'' group, that illustrated the in vivo radioimmunoconjugate specificity. A higher level of radiotracer accumulation was observed in the FCS compared with FCR tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to in vitro results, a correlation was observed between EGFR expression and tumor uptake of 89 Zr-DFO-cetuximab by small animal PET/CT imaging as shown in Figure 5. Benedetto 59 previously performed the blocking study, and the small animal PET/CT images have revealed a reduction in uptake profile for ''blocking'' group (with an excess of unlabeling cetuximab) and an intense 89 Zr-DFO-cetuximab uptake in FCS for ''non-blocking'' group, that illustrated the in vivo radioimmunoconjugate specificity. A higher level of radiotracer accumulation was observed in the FCS compared with FCR tumors.…”
Section: Discussionmentioning
confidence: 91%